Handbook of UFO religions - Zeller, Benjamin E. (Brill handbooks on contemporary religion, 2021)
"The Handbook of UFO Religions, edited by esteemed scholar of new religions Benjamin E. Zeller, offers the most expansive and detailed study of the persistent, popular, and global phenomenon of religious engagements with ideas about extraterrestrial life. The present work considers not only new religions founded on ideas about extraterrestrials and UFOs, but how those within more mainstream religions have responded to the science, scientific speculation, and popular culture involving extraterrestrials, UFOs, and related concepts. Global in reach, it includes chapters considering South and East Asia, Europe, and North and South America, and draws on several interdisciplinary methods. In addition, the handbook traces connections between UFO religiosity and cultural patterns such as science and scientism, esoterism and occultism, millennialism, and popular culture. Contributors are: Rafael Antunes Almeida, W. Michael Ashcraft, Stefano Bigliardi, Susannah Crockford, George D. Chryssides, Carole M. Cusack, Regis Dericquebourg, Holly Folk, David J. Halperin, Olav Hammer, Kelly E. Hayes, Joseph P. Laycock , Layne Little, Paul O. Myhre, Erik A. W. Östling, Susan J. Palmer, Lukas Pokorny, David G. Robertson, Mikael Rothstein, Christa Shusko, Karen Swartz, Diana Tumminia, Hugh B. Urban, and Franz Winter"--